2021
DOI: 10.1007/s00787-021-01859-7
|View full text |Cite
|
Sign up to set email alerts
|

Informative value of referral letters from general practice for child and adolescent mental healthcare

Abstract: Although referral letters (RLs) form a nodal point in a patient’s care journey, little is known about their informative value in child and adolescent mental healthcare. To determine the informative value of RLs to child and adolescent psychiatry, we conducted a chart review in medical records of minors registered at specialized mental healthcare between January 2015 and December 2017 (The Netherlands). Symptoms indicated in RLs originating from general practice (N = 723) were coded and cross-tabulated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…People were confused about how, from whom, and where to seek help (Radez et al, 2021 ). We found healthcare professionals, family members, and peers who had previous experience seeking mental healthcare influenced the care-seeking behaviour of people who were unfamiliar with services (Aydin et al, 2021 ). Service use is also influenced by an individual’s ability to have decision-making power and affordability (Hajjaj et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…People were confused about how, from whom, and where to seek help (Radez et al, 2021 ). We found healthcare professionals, family members, and peers who had previous experience seeking mental healthcare influenced the care-seeking behaviour of people who were unfamiliar with services (Aydin et al, 2021 ). Service use is also influenced by an individual’s ability to have decision-making power and affordability (Hajjaj et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aydin et al and Hayes et al describe strategies that may improve diagnostic practices and patient engagement in child psychiatry [ 1 , 2 ]. Aydin et al conducted a chart review ( N = 723) of patients treated at specialised mental health care in the Netherlands between 2015 and 2017 and explored the diagnostic informative value of referral letters to child and adolescent psychiatry from general practitioners [ 1 ].…”
mentioning
confidence: 99%
“…Aydin et al and Hayes et al describe strategies that may improve diagnostic practices and patient engagement in child psychiatry [ 1 , 2 ]. Aydin et al conducted a chart review ( N = 723) of patients treated at specialised mental health care in the Netherlands between 2015 and 2017 and explored the diagnostic informative value of referral letters to child and adolescent psychiatry from general practitioners [ 1 ]. They found that diagnostic classification was aligned with at least one reason for referral in over half of the cases and had the highest predictive value for predicting eating disorders and the lowest for behavioural problems.…”
mentioning
confidence: 99%